Gregory the Great and Eustratius of Constantinople: The Dialogues on the Miracles of the Italian Fathers as an Apology for the Cult of Saints - Dal Santo, Matthew (Journal of early Christian studies, 2009)
This paper argues that Gregory the Great's Dialogues on the Miracles of the Italian Fathers (ca. 593) represent an apology for the cult of the saints comparable to Eustratius of Constantinople's On the State of Souls after Death (ca. 582). Gregory and Eustratius were contemporaries during Gregory's stay in the imperial capital as papal apocrisarius (ca. 579-86). Both writers defended the actuality of the saints' miracles against sixth-century doubters who possibly deemed the cult of the saints idolatrous. Like Eustratius, Gregory proposed a cooperation of energies between God and the holy man which allowed miracles to be conceived as both a divine and human event that legitimated the saints' veneration. The eschatology which both writers developed to defend the saints' role as mediators was also controversial, particularly their justification of the practice of offering prayers and Masses for the dead. [End Page 421]